Efficacy of organic and inorganic nutrient management on productivity and profitability of Radish - Pooja Devi Meena; R. S. Dhaka (Annals of Agricultural Research, 2022)
A field experiment entitled “Efficacy of organic and inorganic fertilizers on growth, yield and profitability of Radish [Raphanus sativus L.]” was conducted at Horticulture Farm, MJRP College of Agriculture & Research, Achrol during Rabi season, 2016-17. It consisted of 15 treatment combinations with five levels of organic manure (Control, FYM @ 10 t/ha, FYM @ 15 t/ha, vermicompost @ 5 t/ha and vermicompost @ 7.5 t/ ha) and three levels of inorganic fertilizers (Control, 75% RDF and 100% RDF) in Randomized Block Design with three replications. The application of vermicompost @ 7.5 t/ha among the different treatments of organic manures proved significantly superior over rest of the treatments in respect to plant height (37.16 cm), number of leaves per plant (11.45), fresh weight of root (195.96 g), diameter of root (4.36 cm), root yield per ha (257.46 q/ha), nitrogen (1.521%), phosphorus (0.561%) and sulphur (0.227%) content in root, maximum net return (Rs.248496/ha) and B:C (2.86) ratio as compared to control. Similarly, results showed that application of 100 percent RDF also significantly enhanced the plant height (37.31 cm), number of leaves per plant(11.61), fresh weight of root (199.05 g), diameter of root (4.54 cm), root yield per ha (255.02 q/ha), nitrogen (1.460%), phosphorus (0.549%) and sulphur (0.222%) content in root, TSS (7.41%) content in roots, net return (Rs.256476/ha ) and B:C (3.39) ratio as compared to control.